On one bifurcation in relaxation systems - Kolesov, A. Yu.; Mishchenko, E. F.; Rozov, N. Kh. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We establish conditions under which, in three-dimensional relaxation systems of the form x = f(x, y, μ),, εy = g(x, y),x= (x_1, x_2) R^2,yR , where 0 < ε